E-learning for mobile learning platform - MacInnes, Catriona (2015)
It could be argued that to learn is the fundamental purpose of life. All human beings are born without any knowledge of the world around us; they must learn to talk, to walk. From the very beginning of life, people are adapting and learning subconsciously. By studying the way people learn, methods can be created to increase learning potential and efficiency. With the progression of technology in this day and age a number of people have access to the Internet and a computer, learning is being brought to these platforms. E-learning systems are advantageous in that they can be accessed from wherever a user has a computer and the internet however as this can often be unsupervised learning, it leaves a gap open for users to ‘game’ the system and for those that are struggling to potentially be left behind. In these situations, the E-learning system does not help the users learning, it hinders it. Students that abuse the system lower the integrity of this method of teaching and negatively impact their education. Developing an e-learning system that tutors students while simultaneously gathering information about their behaviour and motivation while undertaking the task can be used to classify and sort the way a student studies based on behavioural markers. Understanding the model used to classify this kind of data is very important. By doing so, it can provide insight into how knowledge can be measured and provide a gateway to developing and creating future models. This is not a new idea, however the algorithms being used to data mine the algorithms are, and they are constantly being inspired by each other. The Four models used in this paper have all got similar ideas and modelling within them but perform in different ways.